Incidental thyroid nodules on thoracic contrast-enhanced computed tomography in clinical practice during a 10-year period: Characteristics, clinical outcomes, and factors contributing to further evaluation. Issue 11 (March 2017) - Park, Ju Yong; Lee, Kyung Hee; Cho, Soon Gu; Kim, Yeo Ju; Lee, Ha Young; Hong, In Ki; Kim, Jun Ho
Abstract : Abstract: The purposes of this study were to assess the prevalence, malignancy rate, and characteristics of incidental thyroid nodules (ITNs), and to identify factors that contribute the additional workup by ultrasound. The medical records and imaging features of ITNs reported via thoracic computed tomography (CT) were retrospectively reviewed to determine the size, multiplicity, attenuation, shape, and presence of calcification. To identify the factors associated with additional workup, we compared the workup and non-workup groups in terms of nodule characteristics, indications, and CT slices. We identified factors that could distinguish malignant ITNs from non-malignant nodules. A total of 60, 921 thoracic CT scans met the inclusion criteria, and ITNs were reported using formal radiology in 2733 patients (4.5%). Among all patients with reported ITNs, 546 (20.0%) underwent further workup. Of these patients, 62 (2.3%, 62/2773) were diagnosed with malignant nodules. Multivariable analysis identified multiple factors associated with additional workup, including female sex, younger age, larger nodule size, calcification, anteroposterior to transverse dimension ratio >1, heterogeneous attenuation in the nodule, and scanning indications such as infection or screening. However, only calcification was associated with malignant nodules (odds ratio [OR] = 2.313; 95% confidence interval [CI], 1.301–4.113). We observed discordance between the numbers of reported ITNs and case with additional workup and identified multiple factors associated with additional workup. We have, therefore, demonstrated a need for reliable subsequent evaluation guidelines and note that the appearance of calcification in an ITN on imaging may be a factor indicating the need for additional workup.